EFL TEACHER’S AUDIO FEEDBACK IN IMPROVING ENGLISH WRITING SKILLS: SECONDARY STUDENTS’ PERCEPTION AND MOTIVATION - Doni Mulia Putra; Uun Muhaji; Ayu Liskinasih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Teacher feedback plays an important role in supporting students' learning, yet both direct and indirect feedback have limitations in helping students understand and apply feedback during revision. In English as a Foreign Language (EFL) classroom, these challenges are associated with unclarity and incomplete feedback delivery. Audio feedback has been proposed as a complementary strategy to address these issues. Although widely investigated, previous studies have mainly focused on tertiary students, while evidence from Indonesian secondary schools remains limited. Therefore, this study examined Indonesian junior secondary EFL students' perceptions of audio feedback in English writing classes in terms of clarity, usefulness, and motivation. This qualitative case study involved six participants to capture the natural process of feedback, including five eighth-grade students as the focus area and one English teacher to provide the instructional viewpoints. Data were collected through reflection journals, writing assignments, teacher audio recordings, and semi-structured interviews. The findings revealed that students perceived audio feedback as insufficient to support feedback clarity due to language inaccessibility and employed a more effective feedback strategy based on students’ linguistic readiness rather than audio form delivery. English proficiency also influenced students’ ability to interpret and apply the feedback to produce useful knowledge. Furthermore, motivation to revise writing was shaped more by students' perceived competence and emotional responses than by the audio delivery mode itself. This study concludes that audio feedback will be more effective when the teacher utilizes accessible language, adjusts to students' proficiency levels, and provides emotionally supportive setting so that students can produce useful knowledge in improving English writing skills. ABSTRAK Umpan balik guru berperan penting dalam mendukung perkembangan belajar siswa, tetapi metode langsung maupun tidak langsung masih memiliki keterbatasan dalam membantu siswa memahami dan menerapkan umpan balik pada proses revisi. Dalam pembelajaran bahasa Inggris sebagai bahasa asing (English as a Foreign Language/EFL), kendala tersebut dipengaruhi oleh kemampuan kognitif siswa dan penyampaian umpan balik yang kurang tepat. Audio feedback diusulkan sebagai strategi pelengkap untuk mengatasi permasalahan tersebut. Meskipun telah banyak diteliti, sebagian besar penelitian berfokus pada mahasiswa, sedangkan kajian pada siswa sekolah menengah di Indonesia masih terbatas. Oleh karena itu, penelitian ini mengkaji persepsi siswa EFL sekolah menengah pertama di Indonesia terhadap penggunaan audio feedback dalam pembelajaran menulis berdasarkan aspek kejelasan, kemanfaatan, dan motivasi. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus yang melibatkan enam partisipan untuk mendapatkan gambaran proses alami umpan balik, terdiri atas lima siswa kelas VIII yang mejadi fokus utama dan seorang guru bahasa Inggris untuk memberikan perspektif dari sisi pengajar. Data dikumpulkan melalui jurnal refleksi, tugas menulis, rekaman audio feedback, dan wawancara semi-terstruktur. Hasil penelitian menunjukkan bahwa siswa memandang audio feedback membantu memperjelas umpan balik guru apabila bahasanya mudah dipahami dan didukung dengan strategi umpan balik yang lebih efektif, bukan semata-mata karena bentuk medianya. Tingkat kemahiran berbahasa Inggris turut memengaruhi kemampuan siswa dalam memahami dan menerapkan umpan balik untuk mengasilkan pengetahuan yang bermanfaat. Selain itu, motivasi merevisi tulisan lebih dipengaruhi oleh persepsi terhadap kemampuan diri dan respons emosional dibandingkan dengan penyampaian melalui audio. Penelitian ini menyimpulkan bahwa audio feedback akan lebih efektif apabila guru menggunakan bahasa yang mudah dipahami, disesuaikan dengan tingkat kemahiran siswa, serta mendukung kondisi emosional mereka sehingga dapat menghasilkan ilmu yang bermanfaat dalam meningkatkan kemampuan menulis Bahasa Inggris.